2007
DOI: 10.5367/000000007780007326
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Entrepreneurs and Spheres of Inter-Firm Relations

Abstract: A relatively small body of literature in tourism concentrates on the issues of small firms and entrepreneurs and ‘this area of inquiry is vastly under-researched’ (Thomas, 2004, p 1). A key piece of research (Rimmington et al, 1999) classifies entrepreneurs in the tourism sector, and one category that has received research attention has been that of lifestyle entrepreneurs. This article outlines the literature on lifestyle entrepreneurs and concludes that much of the focus to date has been on the indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 24 publications
1
42
0
1
Order By: Relevance
“…What is perhaps the most interesting common factor found to hold true across economies was a conscious rejection, or disentangling (Mottiar 2007), by LOST firms of conventional economic business models justified on the basis of standard performance indicators, such as employment growth, profit maximization, and market orientation. LOST firm operators appear to recognize the strategic value of, for example:…”
Section: Achievement Of a Desired Lifestyle And A Bridge Tomentioning
confidence: 97%
See 1 more Smart Citation
“…What is perhaps the most interesting common factor found to hold true across economies was a conscious rejection, or disentangling (Mottiar 2007), by LOST firms of conventional economic business models justified on the basis of standard performance indicators, such as employment growth, profit maximization, and market orientation. LOST firm operators appear to recognize the strategic value of, for example:…”
Section: Achievement Of a Desired Lifestyle And A Bridge Tomentioning
confidence: 97%
“…In particular, they emphasize the importance of lifestyle motives within tourism entrepreneurship as being a significant feature of small firms in this sector. Other authors have added weight to the call for greater research and understanding relative to the centrality of lifestyle as a distinguishing feature of small tourism firms (for example, Page et al 1999;Morrison et al 1999;Ateljevic and Doorne 2000;Ioannides and Petersen 2003;Getz et al 2004;Thomas 2004;Weber 2006;Mottiar 2007). …”
Section: Introductionmentioning
confidence: 97%
“…Besides these, scholars linked other issues with a lifestyle orientation, such as the role of innovation (Ioannides and Petersen, 2003), or inter-firm relations (Mottiar, 2007). This paper considers those as outcomes of entrepreneurial orientation and, as such, they will not be analysed.…”
Section: Theorising Lifestyle Entrepreneurshipmentioning
confidence: 99%
“…Twenty years after their study small tourism and hospitality firms are often generically described as lifestyle enterprises (for example, Ateljevic and Doorne, 2000;Getz and Petersen, 2005;Ioannides and Petersen, 2003;Lashley and Rowson, 2010;Morrison et al, 2001;Mottiar, 2007;Shaw and Williams, 2004). These studies revealed numerous characteristics associated with lifestyle entrepreneurs including: non existence of management strategies and limited return-on-investment based strategies (Morrison, et al, 2001); lack of involvement in formal organisations (Mottiar, 2007); low education and training, and the lack of skills (Lashley and Rowson, 2010); limited innovative strategies (Ioannides and Petersen, 2003); and entry is often related with a lifestyle choice, such as to move to certain place or 'to be my own boss ' (Getz and Petersen, 2005). Nevertheless, the majority of those studies were conducted within the context of western developed economies, with a paucity of studies focusing on transition and developing countries (Morrison, et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Lifestyle entrepreneurs set up businesses in order to maintain a comfortable and exiting lifestyle [34,35]. They are often driven by non-monetary incentives such as tax benefits, personal standards, and independence.…”
Section: Lifestyle Entrepreneursmentioning
confidence: 99%